2015
DOI: 10.4238/2015.december.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hemocyanin from the mud crab Scylla paramamosain and its expression analysis in different tissues, at various stages, and under Vibrio parahaemolyticus infection

Abstract: ABSTRACT.Hemocyanin is an important respiratory protein in many arthropod and mollusk species. Here, four cDNAs (SpHc1, SpHc2, SpHc3, and SpHc4), encoding distinct hemocyanin subunits from Scylla paramamosain were cloned using EST analyses and the rapid amplification of cDNA ends. The four full-length cDNA fragments (SpHc1-4) were 2281, 2002, 2184, and 2069 bp, respectively, and they encoded four putative proteins (570-676 amino acids) with a molecular mass of ~65.0-76.8 kDa. Quantitative real-time PCR analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As part of the ongoing effort to support and enhance the aquaculture of Scylla species, much work has focused on understanding the biology of these crabs (e.g., Bao et al, 2015;Chen et al, 2015;Girish et al, 2015;Gong et al, 2015;Huang et al, 2014Huang et al, , 2015Ikhwanuddin et al, 2014;Kornthong et al, 2014;Sun et al, 2015;Wang et al, 2015aWang et al, , 2015bXie et al, 2014;Zeng et al, 2016;Zhao et al, 2015). One outcome of these studies has been the development of extensive transcriptomic resources for several Scylla species (e.g., Bao et al, 2015;Kornthong et al, 2014;Ma et al, 2014;Xie et al, 2014), including S. olivacea, for which approximately 160,000 transcriptome shotgun assembly (TSA) sequences are now available in GenBank (e.g., BioProject Accession No.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the ongoing effort to support and enhance the aquaculture of Scylla species, much work has focused on understanding the biology of these crabs (e.g., Bao et al, 2015;Chen et al, 2015;Girish et al, 2015;Gong et al, 2015;Huang et al, 2014Huang et al, , 2015Ikhwanuddin et al, 2014;Kornthong et al, 2014;Sun et al, 2015;Wang et al, 2015aWang et al, , 2015bXie et al, 2014;Zeng et al, 2016;Zhao et al, 2015). One outcome of these studies has been the development of extensive transcriptomic resources for several Scylla species (e.g., Bao et al, 2015;Kornthong et al, 2014;Ma et al, 2014;Xie et al, 2014), including S. olivacea, for which approximately 160,000 transcriptome shotgun assembly (TSA) sequences are now available in GenBank (e.g., BioProject Accession No.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, horse crab Portunus trituberculatus and mangrove crab Scylla serrata reportedly have five types of monomeric arthropod haemocyanin subunits [36,37]. Some crustaceans express distinct haemocyanin subunits during certain developmental stages, or synthesise such subunits in response to certain physiological conditions [38]. Many researchers have reported that the expression levels of hemocyanin genes are affected by bacterial or viral infection [30,38].…”
Section: Preparation Of Haemocyanin and Its Subunitsmentioning
confidence: 99%
“…Some crustaceans express distinct haemocyanin subunits during certain developmental stages, or synthesise such subunits in response to certain physiological conditions [38]. Many researchers have reported that the expression levels of hemocyanin genes are affected by bacterial or viral infection [30,38]. These data could explain the presence of a different number of glycosylated haemocyanin subunits in the haemolymph of E. verrucosa.…”
Section: Preparation Of Haemocyanin and Its Subunitsmentioning
confidence: 99%